Walk-Through Illustrations: Frame-Coherent Pen-and-Ink Style in a Game Engine - Freudenberg, Bert; Masuch, Maic; Strothotte, Thomas (Computer graphics forum, 2001)
In this paper we show how a game engine designed to generate photorealistic images can be extended to produce non‐photorealistic and hybrid renditions. We introduce new hardware‐based methods to accomplish pen‐and‐ink illustrations. The combination of the highly optimized processing of a game engine and the use of hardware for NPR algorithms yields real‐time animation of pen‐and‐ink illustrations. The particular advance of this method is that it yields the first real‐time, frame‐coherent pen‐and‐ink animations which maintain both tone and texture.